Structural plasticity and reorganisation in chronic pain - Kuner, Rohini; Flor, Herta (Nature reviews. Neuroscience, 2017)
Chronic pain is not simply a temporal continuum of acute pain. Studies on functional plasticity in neural circuits of pain have provided mechanistic insights and linked various modulatory factors to a change in perception and behaviour. However, plasticity also occurs in the context of structural remodelling and reorganisation of synapses, cells and circuits, potentially contributing to the long-term nature of chronic pain. This Review discusses maladaptive structural plasticity in neural circuits of pain, spanning multiple anatomical and spatial scales in animal models and human patients, and addresses key questions on structure-function relationships.